Formulation of the Ex-PNPM-MPd Activity Management Units (UPKs) Institutional Model in East Java - Hadi Sulistyo; V Rudi Handoko (Wacana Journal of Social and Humanity Studies, 2021)
This study aimed to compile the Formulation of the Ex-PNPM-MPd Activity Management Units (UPKs) Institutional Model in East Java. The descriptive research method was applied. The research subjects were the ex-PNPM-MPd UPK institutions in East Java. This research produced the best formulation of the Ex PNPNM-MPd UPK institutional model, where the institution must remain 1) prioritizing community’s needs- and conditions-based empowerment activities and community’s needs in its working area, 2) seeking legality for institutions and business units, 3) having an institutional structure that can cover all institutional activities, 4) implementing a merit system, namely HR policies and management based on qualifications, competencies, and performance fairly, 5) compiling and publishing regular financial reports based on financial standards in a transparent and accountable manner, 6) striving for development revolving fund activities (savings and loans unit) by increasing profit targets (surplus/SHU), increasing the number of beneficiaries (Poor Households (RTM)/non-RTM groups) and innovating savings and loans product services, and 7) developing non-revolving fund business units by expanding the market, introducing the brand (trademark) and applying a sound business management system.